ELSA 2016 Cohort: Alcohol, Tobacco, and Marijuana Use and Their Association with Age of Drug Use Onset, Risk Perception, and Social Norms in Argentinean College Freshmen - Pilatti, Angelina; Read, Jennifer P.; Pautassi, Ricardo M. (Frontiers in Psychology, 2017)
The transition from high school to college is a high-risk stage for the initiation and escalation of substance use. Substance use and its associated risk factors have been thoroughly described in developed countries, such as the United States, but largely neglected in Argentina, a South American country with patterns of a collectivist culture. The present cross-sectional study describes the occurrence of alcohol, tobacco, and marijuana use and the association between these behaviors and the age of onset of substance use and cognitive (i.e., risk perception) and social (i.e., prescriptive) variables in a large sample of Argentinean college freshmen (n = 4083, 40.1% men; mean age = 19.39 ± 2.18 years). The response rate across courses was ≥ 90% and was similarly distributed across sex. Participants completed a survey that measured substance use (alcohol [with a focus on heavy drinking and binge drinking behaviors], tobacco, and marijuana), age of onset of the use of each substance, perceived risk associated with various substance use behaviors, prescriptive norms associated with substance use, and descriptive norms for alcohol use. The results indicated that alcohol use is nearly normative (90.4% and 80.3% with last year and last month use, respectively) in this population, and heavy drinking is highly prevalent (68.6% and 54.9% with heavy episodic and binge drinking, respectively), especially among those with an early drinking onset (97.8% and 93.6% with last year and last month use and 87.8% and 76.3% with heavy episodic and binge drinking, respectively). The last-year occurrence of tobacco and marijuana use was 36% and 28%, respectively. Early substance use was associated with the greater use of that specific substance. The students overestimated their same-sex friend’s alcohol use, and women overestimated the level of alcohol use of their best male friend. At the multivariate level, all of the predictors, with the exception of the parents’ prescriptive norms, significantly explained the frequency of marijuana and tobacco use and frequency of hazardous drinking. Overall, despite important cultural and contextual differences between Argentina and the United States, our findings suggest that certain vulnerability factors have a similar influence across these cultural contexts.